Tactile exploration and imagery elicit distinct neural dynamics in the parietal cortical network - Zhang, Qi; Yang, Yang; Wang, Zhemeng; Zhou, Jiayue; Gao, Runshi; Yang, Xingyi; Li, Siwei; Yu, Tao; Zhou, Jin; Wang, Changyong (Frontiers in Neuroscience, 2025)
BackgroundTactile imagery involves the reconstruction of sensory experiences without actual tactile input. While tactile perception and imagery exhibit similar spatial patterns of neural activation, the underlying neural dynamics, particularly cortical communications within the parietal network, remain unclear.MethodsThe present study recruited 5 patients with implanted stereo-electroencephalography (sEEG) electrodes and recorded sEEG data during texture scanning and imagery. Local neural representations and interregional communications among parietal cortical regions were analyzed.ResultsOpposing modulation patterns of local time-frequency representations were observed, with inhibited neural synchronization during texture scanning and activated synchronization during texture imagery. Consistently, the directional communication from the somatosensory cortex to the posterior parietal cortex (PPC) was found to be suppressed for scanning but enhanced for imagery. Additionally, bidirectional communication between the supramarginal gyrus and precuneus was activated during imagery but not scanning, suggesting a unique pathway for reconstructing tactile experiences.ConclusionOur findings proposed that while texture perception and imagery engage overlapping cortical regions, their mechanisms underlying local encoding and interregional communication are distinct.